2023
DOI: 10.3389/fphys.2023.1076730
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic and gender disparity in the severity of NAFLD among people with diabetes or prediabetes

Abstract: Aim: Non-alcoholic fatty liver disease (NAFLD) exhibits a racial disparity. We examined the prevalence and the association between race, gender, and NAFLD among prediabetes and diabetes populations among adults in the United States.Methods: We analyzed data for 3,190 individuals ≥18 years old from the National Health and Nutrition Examination Survey (NHANES) 2017–2018. NAFLD was diagnosed by FibroScan® using controlled attenuation parameter (CAP) values: S0 (none) < 238, S1 (mild) = 238–259, S2 (moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Studies have found that within Hispanic populations in the United States, the prevalence of MASLD is higher in those of Mexican origin [12] . A study published in 2020 analyzed 4,538 adult participants from the National Health and Nutrition Examination Survey (NHANES) from 2011-2016 in the United States found that MASLD prevalence was highest among Mexican Americans (48.4%), and lowest among non-Hispanic Black individuals (8.0%) and Asians (18.1%) [19] . Another study utilizing NHANES data from 2017-2018 investigated 3,190 adults (categorized as normoglycemic, prediabetic, or diabetic) and found that Mexican American men had the highest prevalence of severe MASLD (defined as controlled attenuation parameter [CAP] score > 290 dB/m) in the normoglycemic and diabetic populations compared to non-Hispanic White, non-Hispanic Black, and other Hispanic groups [20] .…”
Section: Higher Prevalence Of Masld Among Mexican-american Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that within Hispanic populations in the United States, the prevalence of MASLD is higher in those of Mexican origin [12] . A study published in 2020 analyzed 4,538 adult participants from the National Health and Nutrition Examination Survey (NHANES) from 2011-2016 in the United States found that MASLD prevalence was highest among Mexican Americans (48.4%), and lowest among non-Hispanic Black individuals (8.0%) and Asians (18.1%) [19] . Another study utilizing NHANES data from 2017-2018 investigated 3,190 adults (categorized as normoglycemic, prediabetic, or diabetic) and found that Mexican American men had the highest prevalence of severe MASLD (defined as controlled attenuation parameter [CAP] score > 290 dB/m) in the normoglycemic and diabetic populations compared to non-Hispanic White, non-Hispanic Black, and other Hispanic groups [20] .…”
Section: Higher Prevalence Of Masld Among Mexican-american Populationsmentioning
confidence: 99%
“…In the United States, Hispanic individuals have the highest prevalence of MASLD, followed by non-Hispanic White individuals and then non-Hispanic Black individuals [2,[11][12][13][14][15] Of patients with biopsy-proven MASLD, the frequency of MASH varies by race and ethnicity with highest frequency in Hispanic individuals, then non-Hlispanic White individuals, and then non-Hispanic Black individuals and Asian individuals [16] The largest rate of increase of hospital admissions with MASLD was found amongst Hispanic individuals, followed by non-Hispanic White individuals andthen non Hispanic Black individuals [18] Within Hispanic populations in the United States, the prevalence of MASLD is higlher in those of Mexican origin [12,15,19,20] Similar trends are found among young adults and adolescent populatiorns with Hispanic individuals having a significantly higher prevalence of MASLD than non Hispanic individuals [21,22] Non-Hispanic Black individuals are less likely to develop MASLD tthan non-Hispanic White individuals [25,26] MASH: Metabolic Dysfunction-associated Steatohepatitis; MASLD: Metabolic dysfunction-associated steatotic liver disease.…”
Section: Key Finding Sourcesmentioning
confidence: 99%
“…While comprehensive data on the global burden of prediabetes are lacking, the International Diabetes Federation estimates a global prevalence of Impaired Glucose Tolerance (IGT) of 7.5% (374 million adults), of whom 72.2% reside in low-and middle-income countries (LMICs). Ethnicity is a known modifier of metabolic risk in individuals with prediabetes (3,4); in particular, Mexican mestizo populations have an increased risk of diabetes, which manifests at younger ages and lower body-mass index levels (5)(6)(7). However, epidemiological data on prediabetes among ethnically diverse populations are limited, including in Mexico, where diabetes mellitus is a leading cause of disability and death (8).…”
Section: Introductionmentioning
confidence: 99%